Moderation Effects of Ethnic-Racial Identity on Disordered Eating and Ethnicity Among Asian and Caucasian Americans - Obleada, Katrina T.; Bennett, Brooke L. (Frontiers in Psychology, 2021)
Background: The current study was designed to examine whether ethnic-racial identity moderated the relationship between disordered eating and primary ethnic identification. Methods: Three hundred and ninety-eight undergraduate females (Mage = 19.95, SD = 3.09) were recruited from a large university in Hawai‘i. Participants completed the Eating Disorder Examination Questionnaire, the Ethnic-Racial Identity measure (ERI), and reported their primary ethnicity as an index of ethnicity. Results: There was a significant correlation between eating concerns and centrality r(357) = .127, p < .05. Moderation analyses indicated that only ERI centrality moderated the predictive effect of ethnicity on the importance of eating concerns, b =.05, t(347) = 2.37, p=.018. Conclusions: Results suggest the relationship between self-reported primary ethnicity and EDEQ scores is greater when ethnicity is more central to the individual’s identity or when in-group affect is important to an individual. Findings warrant further research on the underlying mechanisms that account for the differing ways ethnic-racial identity may affect eating concerns.